Diphenylphosphine‐Oxide‐Fused and Diphenylphosphine‐Fused Porphyrins: Synthesis, Tunable Electronic Properties, and Formation of Cofacial Dimers. Issue 28 (24th April 2017) - Fujimoto, Keisuke; Kasuga, Yuko; Fukui, Norihito; Osuka, Atsuhiro
Abstract: Diphenylphosphine‐oxide‐fused Ni II porphyrin8 was synthesized from 3, 5, 7‐trichloroporphyrin5 via a reaction sequence of nucleophilic aromatic substitution with lithium diphenylphosphide, oxidation with H2 O2, and palladium‐catalyzed intramolecular cyclization. Reduction of8 with HSiCl3 gave diphenylphosphine‐fused Ni II porphyrin9 . The embedded P=O and P moieties serve as a strong electron‐accepting and electron‐donating group to perturb the optical and electrochemical properties of the Ni II porphyrin. Ni II porphyrin9 is diamagnetic with a low‐spin Ni II center in solution but becomes paramagnetic with a five‐coordinated Ni II center with high‐spin ( S= 1) state in the solid state. Diphenylphosphine‐oxide‐fused Zn II porphyrin10 was also synthesized and shown to form a face‐to‐face dimer with mutual O‐Zn bonds in the crystal and in nonpolar and moderately polar solvents. The dimerization of10 in CDCl3 has been revealed to be an entropy‐driven process with a large entropy gain (Δ S D =207 J K −1 mol −1 ). Abstract : High spin : Diphenylphosphine‐oxide‐fused Ni II porphyrin and diphenylphosphine‐fused Ni II porphyrin were prepared (left), in which the embedded P=O and P moieties serve as a strong electron‐accepting and electron‐donating group. The latter is diamagnetic with a low‐spin Ni II center in solution but becomes paramagnetic with a high‐spin ( S= 1) Ni II center in the solid state. Diphenylphosphine‐oxide‐fused Zn II porphyrin (right) showed entropically driven dimerization in CDCl3 .